DETERMINAN KINERJA KEUANGAN REVOLVING LOAN FUND: STUDI KASUS PADA UNIT PENGELOLA KEUANGAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERKOTAAN KABUPATEN GRESIK - Haryanto, Haryanto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The aim of this study was to obtain empirical evidence about the determinants of financial performance Revolving Loan Fund (RLF) with independent variable institutional BKM, personnel officer UPK, the outpouring of time UPK, Incentives UPK, revolving capital UPK and idle Money on financial performance Revolving Loan Fund (RLF) which consists of LAR, PAR, CCR and ROI as the dependent variable. Statistical analysis by the method of Multinomial Logistic Regression showed that together these research variables have an influence on the financial performance of revolving loans (revolving loan fund). Partially statistically significant variables are: institutional variables BKM (KLB), and the outpouringof Time UPK (CWU). Keywords: Determinants of Financial Performance Revolving Loan Fund